Subacute neuronopathy in a young man: a possible association with tetracycline treatment - Björn Lindvall; Charlotte Dahle; Magnus Vrethem (MDPI AG, 2011)
A young man with subacute neuronopathy following tetracycline treatment is described. The symptoms started as a sensory dorsal root affection but by time also involved motor nerves. He developed a severe sensory ataxia with pseudoathetotic movements. Other possible aetiologies were scrutinized and excluded. Tetracycline induced neuronopathy is hitherto not reported in the literature. We propose a possible association between treatment with tetracycline and the development of sensory neuronopathy in this patient.